A Study on Microbial Fuel Cell (MFC) to Power Underwater Monitoring Device - Saravanan, Ravichanthiran (2018)
A "Microbial Fuel Cell" also known as biological fuel cell impersonates the way bacteria behave in nature to generate current. A Microbial Fuel Cell converts the chemical energy through a catalytic reaction to electrical energy. A Microbial Fuel Cell consists of two different compartments namely an anode and cathode respectively. This project is done by using two compartments which are divided by a cation specific membrane which contains positively charged ions. In the anode, protons and electrons are produced as a result if the fuel oxidization by microorganisms. While the protons are moved to the anode via the membrane the electrons are them moved to the cathode via an external circuit. In the cathode, both protons and electrons are used up to make a combination with oxygen in order to produce water. Malaysia has access to various renewable resources such as wind, ocean, biomass, solar and small hydro. Malaysia therefore has the potential to achieve sustainable energy. Several energy policies have been put in place to promote energy efficiency, quality of service and environmental safeguarding. However there is still no proper collaboration between the government and the general public regarding the use of renewable resources at a faster rate. Therefore, the objective of this project is to study and analyse the requirements of a Microbial Fuel Cell to generate electricity, design and implement a Microbial Fuel Cell, validate and quantity the amount if bio-waste required to generate electricity and to validate and quantity the amount of bio-waste required to generate electricity using the Microbial Fuel Cell. Therefore, a system was fabricated following a proper methodology and several experiments was tested our using different kinds of electrodes and resistor. These experiments are mainly to determine the voltages and power density to do further analysis and discussion. The system must able to power an underwater monitoring device that was replace with an LED as less voltage needed to power up those sensors. There is limitation associated to Microbial Fuel Cell which is their low power density. To have a better understanding of the different parameters and to optimize the production costs can be reduced while the power generation can be increased which ongoing improvements. Before Biological Fuel Cells can actually be produced and commercialized, a huge amount of improvements is required.